2023
DOI: 10.1002/smll.202301914
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Vascular Disrupting Dendritic Nanodevice Incorporating Copper Sulfide Nanoparticles for Immune Modulation‐Mediated Combination Tumor Therapy

Abstract: Development of intelligent nanoplatforms that can simultaneously target multiple factors associated with tumor growth and metastasis remains an extreme challenge. Here, an intelligent dendritic nanodevice incorporating both copper sulfide nanoparticles (CuS NPs) and 5,6‐dimethylxanthenone‐4‐acetic acid (DMXAA, a vascular disrupting agent) within the dendrimer internal cavities and surface modified with a targeting agent LyP‐1 peptide is reported. The resulting generation 5 (G5) dendrimer‐based nanodevice, know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…5A). 75 The dendrimer core contained the CuS NPs and an anti-vascular drug, DMXAA. Additionally, the external surface was functionalized with a cancer-targeting peptide, LyP-1.…”
Section: Dendritic Hybrid Npsmentioning
confidence: 99%
“…5A). 75 The dendrimer core contained the CuS NPs and an anti-vascular drug, DMXAA. Additionally, the external surface was functionalized with a cancer-targeting peptide, LyP-1.…”
Section: Dendritic Hybrid Npsmentioning
confidence: 99%
“…[45] An intelligent dendritic nanodevice prepared by Zhang et al combined photothermal therapy to block the two most common pathways of tumor metastasis by destroying the capillaries and lymphatic capillaries around the tumor, thereby preventing tumor metastasis. [46] In addition to destroying capillary lymphatic vessels, eliminating cancer cells in the lymph nodes is also a crucial method for preventing lymph node metastasis. Cabral et al found that smaller NPs (≈30 nm) had better lymph nodetargeting efficiency than larger ones (70-80 nm).…”
Section: Inhibition Of Tumor Angiogenesismentioning
confidence: 99%
“…By elevating the temperature of tumor tissues, PTT can selectively target and eliminate primary tumors . PDT is a targeted therapeutic approach that utilizes photosensitizers, which are activated by specific wavelengths of light to produce ROS, ultimately leading to tumor cell death. , PTT and PDT have been employed for the treatment of diverse cancers, including melanoma, lung cancer, breast cancer, etc. , However, tumor cells may produce SerpinB9 to suppress granzyme B activity, thereby reducing the efficacy of phototherapy. Therefore, overcoming SerpinB9-mediated resistance is the key to improving the effectiveness of phototherapy.…”
Section: Introductionmentioning
confidence: 99%